Teaching strategies for improving youth fitness - Pangrazi, Robert P.; Corbin, Charles B.; American Alliance for Health, Physical Education, Recreation, and Dance (Reston, VA American Alliance for Health, Physical Education, Recreation and Dance, 1994)
Explains Fitnessgram, a comprehensive program for improving youth fitness.
Includes bibliographical references (p. 137-146).
Keywords: Physical fitness for youth; Physical education for children; Exercise for youth